2016
DOI: 10.1038/ncomms13301
|View full text |Cite
|
Sign up to set email alerts
|

Engineered AAA+ proteases reveal principles of proteolysis at the mitochondrial inner membrane

Abstract: The human YME1L protease is a membrane-anchored AAA+ enzyme that controls proteostasis at the inner membrane and intermembrane space of mitochondria. Understanding how YME1L recognizes substrates and catalyses ATP-dependent degradation has been hampered by the presence of an insoluble transmembrane anchor that drives hexamerization of the catalytic domains to form the ATPase active sites. Here, we overcome this limitation by replacing the transmembrane domain with a soluble hexameric coiled coil to produce act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(84 citation statements)
references
References 60 publications
1
83
0
Order By: Relevance
“…However, in vitro studies have been hampered by difficulties in purifying soluble proteases, as individual Yme1p subunits lacking the insoluble transmembrane spans do not assemble into active hexamers [34]. To overcome this, we applied a method used to produce soluble active hexamers of the human YME1L enzyme [24]. A 32-residue hexamerization sequence (cc-hex) [35] was appended to the N-terminus of a construct containing the soluble AAA+ and peptidase domains of S. cerevisiae Yme1p (residues 267–747) to produce hexYme1p.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in vitro studies have been hampered by difficulties in purifying soluble proteases, as individual Yme1p subunits lacking the insoluble transmembrane spans do not assemble into active hexamers [34]. To overcome this, we applied a method used to produce soluble active hexamers of the human YME1L enzyme [24]. A 32-residue hexamerization sequence (cc-hex) [35] was appended to the N-terminus of a construct containing the soluble AAA+ and peptidase domains of S. cerevisiae Yme1p (residues 267–747) to produce hexYme1p.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the power stroke of Yme1p is insufficient to overcome these interactions and so prevent disassembly of the heterohexamer. We have shown previously that the human YME1L protease exhibits a weaker power stroke compared to many other well-studied AAA+ proteases [24]. Alternatively, the formation of the complex may occlude the N-terminus of Tim10 and prevent recognition of the subunit by the protease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 While the molecular nature of i-AAA degrons remains to be elucidated, the study by the Glynn lab identified an F- h - h -F (where h is any hydrophobic residue) as a potential recognition signal for YME1L. 28 It is noteworthy that this motif or its variants are found in ∼40 proteins comprising the IMS and IM subproteomes. 28 Further analyses determined that Yme1 exhibits specificity toward unfolded degrons but does not seem to recognize them in a folded state.…”
Section: I-aaa Proteasementioning
confidence: 99%
“…This is achieved by active unfolding and feeding of the substrate into the enzyme’s catalytic chamber through the complex’s central pore using the energy of ATP hydrolysis. 28 …”
Section: I-aaa Proteasementioning
confidence: 99%